Analysis of Medication, Cost, and Clinical Outcome of Human and Analogue Insulins of Type 2 Diabetes Mellitus at MMC Hospital 2016-2017 - Jayati, Turpuk Mannaria; Anggriani, Yusi; Laksmitawati, Dian Ratih; Waspadji, Sarwono (Poltekkes Kemenkes Kendari, 2021)
Human insulin and analog insulin are available at RS.MMC. The use of analog insulin was more prevalent among doctors between 2016 and 2017. The data collection was conducted retrospectively, taking samples of 132 outpatients type 2 DM using insulin, of which 74 were evaluated for their clinical outcome. The study's goal is to provide information for developing insulin usage guidelines. The medication profile data were collected from the medicine administration at the Hospital Pharmacy Installation. The clinical outcome data, such as fasting plasma glucose (FPG), two-hour postprandial plasma glucose (2HPP), and Hemoglobin A1c (HbA1c), were garnered from the patients’ medical records. The cost data were collected from the outpatients’ payment receipts provided by the Hospital’s Financial Department. Kolmogorov Smirnov normality test was applied in this research. Statistical trials of differences in clinical outcomes and costs using the Kruskal-Wallis test, showed there was a significant difference between human insulin and insulin analogues in terms of clinical outcomes of GDP, GDPP, HbA1c, and cost after follow-up testing with Mann Whitney, showed average cost of using human insulin for 30 days was Rp1,597,066, and analogue was Rp2,497,535 shows that human insulin and analogues differ significantly in terms of cost (p = 0.015).